PENENTUAN KEASAMAN BUAH NENAS VARIETAS CAYENNE SECARA TIDAK MERUSAK MENGGUNAKAN SHORT WAVELENGTH NEAR INFRARED (SW-NIR) SPECTROSCOPY - Diding Suhandy (Jurnal Teknologi & Industri Hasil Pertanian, 2007)
The acidity of pineapple fruit is one of the most important quality parameter determining the consumer acceptance. The objective of this research was to establish a nondestructive determination of acidity in cayenne pineapple fruit using short wavelength near infrared (SW-NIR) spectroscopy. In this research, a number of 124 samples, consisting of 64 samples for calibration and 60 samples for validation sample set were used, respectively. The spectra of pineapples were acquired at one position for each sample in absorbance mode using a portable spectrometer operated at 300-1100 nm. The acidity of pineapples was measured using titration method. Using the Unscrambler, statistical software for multivariate calibration, a correlation between the spectra and the acidity of pineapples will be investigated. Then, a calibration model for determining the acidity of pineapples will be developed. The result showed that the best calibration model was identified for second derivative spectra in the wavelength range of 700-970 nm with R2 = 0.95. Standard error of prediction (SEP) = 0.048 and standard error of calibration (SEC) = 0.024. The validation result showed that its calibration model had low bias. By a 95% confidence t-test there were no significance differences between the acidity measured by the titration method and that predicted by SW-NIR spectroscopy. Keywords:    pineapple, absorbance mode, acidity, near infrared spectroscopy, calibration model